Worldviews and the American West : the life of the place itself - Stewart, Polly, 1943-2013 (Utah State University Press, 2000)
A diverse group of writers and scholars follow the lead of noted folklorist Barre Toelken and consider, from the inside, the ways in which varied cultures in the American West understand and express their relations to the world around them. As Barre Toelken puts it in The Dynamics of Folklore, '''Worldview' refers to the manner in which a culture sees and expresses its relation to the world around it.